The Application of Fertilizer on Various Jajar Legowo System to Rice Growth and Yield - Ellen Rosyelina Sasmita; Siwi Hardiastuti (Jurnal Agrivet, 2017)
The research aims was to compare the effect of the use of inorganic fertilizer which combined with organic fertilizer on various cropping systems of jajar legowo plant toward the growth and yield of rice plants. The research methods used Split Plot by using Randomized Complete Block Design with three replications. The main plot is fertilizer type, comprises of three levels, P1 = 100% inorganic fertilizer (Phonska 600 kg/ha), P2 = 50% inorganic fertilizer + 10 ton/ha BATAN’s bio-organic fertilizer and P3 = 50% inorganic fertilizer + 10 ton/ha Faperta UPN “Veteran” Yogyakarta’s organic fertilizer. Sub plot was jajar legowo system, comprises of three levels, J1 = Jajar Legowo 2:1, J2 = Jajar Legowo 3:1 and J3 = Jajar Legowo 4:1. The results showed that there was no interaction between fertilizer type and jajar legowo system on rice growth and yield. There was no significant difference between 100% inorganic fertilizer with 50% inorganic + organic BATAN fertilizer and 50% inorganic + organic FP UPN fertilizer on plant height after 56 days of planting, the number of productive tillers, panicle length, the weight of 1000 grains and yield. The three jajar legowo system did not give significant influence on plant height; jajar legowo 4:1 system produced more tillers and the number of productive tillers is greater than jajar legowo 2:1 and 3:1. Jajar legowo system 2:1 produced higher yield than jajar legowo system 3:1 and 4:1.Keywords: fertilizer, jajar legowo, rice